From Custom to Management: Cikondang Leadership and Decision-Making Patterns - Nazma Aulia Surrahman; Muhammad Raffa El Hilaby; Sulthan Farid Hariz; Melindha Cah Yani Putri Dwi Yanto; Muhammad Daffa Apriliansyah (Publikasi Indonesia, 2026)
This research is grounded in the expanding crisis of leadership in modern organizations, characterized by rigid bureaucracy and impersonal managerial approaches. Conversely, indigenous communities such as Cikondang in Bandung Regency have for centuries practiced sustainable collective leadership and consensus-based decision-making systems. The gap between these two realities raises fundamental questions about how local wisdom can contribute to contemporary leadership thought. This study examines the transformation of leadership patterns and decision-making mechanisms in the Cikondang indigenous community and their relevance to modern management practices. The Cikondang community is known for its leadership structure based on customary values, deliberation, and local wisdom passed down through generations. Through a qualitative approach involving literature review and document analysis, this study demonstrates that Cikondang indigenous leadership is characterized by collectivity, moral legitimacy, and an orientation toward social harmony. These patterns are then compared with contemporary management principles, particularly in the areas of participatory leadership, conflict management, and consensus-based decision-making. The results reveal that Cikondang's indigenous values align with modern management concepts emphasizing collaboration, effective communication, and the strengthening of organizational values. Furthermore, these findings are critically linked to major theories such as Participatory Leadership and Ethical Leadership, as well as sustainable development studies. Therefore, integrating local values into management can provide a more humanistic, adaptive, and sustainable leadership model, while offering an alternative framework for community governance in the modern era.